The Effect of Product Quality and Store Atmosphere on Purchase Decisions at Otsky Bandar Lampung Distro - Sari Santoso, Monique Permata; Roslina, Roslina; Nabila, Nuzul Inas (Pusdikra Publishing, 2023)
Today's society realizes that clothing is more than just clothing needs, but also fashion needs. The shift in clothing style to being a medium to show one's existence in the community has made the clothing business grow rapidly today. Distro is one of the many apparel businesses that have sprung up in Indonesia today, especially in the city of Bandar Lampung. Otsky is a local clothing distribution that is popular with the people of Lampung. Otsky's shop has good product quality and a good store atmosphere. On the other hand, the researchers conducted a survey and found several complaints from consumers about unsatisfactory product quality in terms of materials and product form. Apart from that, there are complaints about the shop atmosphere at Otsky, which has a reasonably dense layout so that it fills the room which affects convenience when shopping. This study aims to determine whether product quality and store atmosphere can influence purchasing decisions at Otsky Stores. The research method used is quantitative, namely a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. This study using a survey method by distributing questionnaires to Otsky Shop buyers. The population of this study were buyers of Otsky Stores in Bandar Lampung and 100 respondents were taken. The results of this study indicate that product quality (X1) and store atmosphere (X2) influence purchasing decisions (Y). The store atmosphere variable shows a result of 0.490, which is higher than the product quality variable, which has an impact of 0.447 on purchasing decisions.